2006
DOI: 10.1007/s11120-006-9100-x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate peroxidase–thioredoxin interaction

Abstract: Proteomics data have suggested ascorbate peroxidase (APX) to be a potential thioredoxin-interacting protein. Using recombinant enzymes, we observed that incubation of pea cytosolic APX with reduced poplar thioredoxins h drastically inactivated the peroxidase. A similar inactivation is induced by reduced glutathione and dithiothreitol, whereas diamide and oxidized glutathione have no effect. Oxygen consumption measurements, modifications of the APX visible spectrum and protection by hydrogen peroxide scavenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In contrast, the decrease of HvNTR2 expression in aleurone layers in response to GA at early incubation time points suggests an initial low level of reduced Trx h and target proteins in the aleurone layer. Several potential Trx target proteins (Yamazaki et al, 2004;Gelhaye et al, 2006) are involved in protection against reactive oxygen species, generated as by-products of lipid metabolism in the aleurone layer (Bethke et al, 2002) and implicated in the initiation of the cell death program (Fath et al, 2001). Down-regulation of HvNTR2 expression by GA is predicted to decrease the proportion of reduced Trx h, resulting in modulation of target protein activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the decrease of HvNTR2 expression in aleurone layers in response to GA at early incubation time points suggests an initial low level of reduced Trx h and target proteins in the aleurone layer. Several potential Trx target proteins (Yamazaki et al, 2004;Gelhaye et al, 2006) are involved in protection against reactive oxygen species, generated as by-products of lipid metabolism in the aleurone layer (Bethke et al, 2002) and implicated in the initiation of the cell death program (Fath et al, 2001). Down-regulation of HvNTR2 expression by GA is predicted to decrease the proportion of reduced Trx h, resulting in modulation of target protein activity.…”
Section: Discussionmentioning
confidence: 99%
“…APX is known as a bi‐specific heme peroxidase that can oxidize either ascorbate or various aromatic small molecules in an H 2 O 2 ‐dependent manner . Sequence alignments revealed that Cys‐32 is the only conserved cysteine residue across all plant cytosolic APXs . Previous studies showed that the chemical modification of Cys‐32 by Ellman's reagent abolished the APX activity toward ascorbate but not other small aromatic substrates .…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Sequence alignments revealed that Cys-32 is the only conserved cysteine residue across all plant cytosolic APXs. 27 Previous studies showed that the chemical modification of Cys-32 by Ellman's reagent abolished the APX activity toward ascorbate but not other small aromatic substrates. 25 Similarly, the APX C32S mutant decreased the ascorbate-oxidizing activity by 70% but had no effects on guaiacol oxidation.…”
mentioning
confidence: 99%
“…Since a reduction of TRX by the photosynthetic electron transfer chain is prevented by DCMU and in the petD mutant, these molecules are candidates for regulators of H 2 O 2 degrading enzymes. Indeed, several H 2 O 2 detoxifying enzymes have been shown to be inactivated by TRXs in vitro (Lemaire et al 2004 ; Gelhaye et al 2006 ). Proteomic studies revealed that also several ROS scavenging enzymes which do not use TRXs as substrates such as catalase, superoxide dismutase, or APX, are putative TRX targets since they are bound to TRX affinity columns (Balmer et al 2004 ; Lemaire et al 2004 ; Maeda et al 2004 ; Wong et al 2004 ; Michelet et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, purified recombinant cytosolic APX from poplar was shown to be inhibited by reduced cytosolic thioredoxin h, reduced glutathione, and dithiothreitol. The molecular mechanism of this inhibition though remains to be determined (Gelhaye et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%